Swedish ABSAbank-Imm 1.0 - Språkbanken Text (University of Gothenburg, 2024)
An annotated Swedish corpus for aspect-based sentiment analysis (a version of Absabank)

Svensk annoterad korpus för aspektbaserad attitydanalys (en version av Absabank)
Svensk ABSAbank-Imm 1.0
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik